2016
DOI: 10.1016/j.socscimed.2016.07.038
|View full text |Cite
|
Sign up to set email alerts
|

“I have to constantly prove to myself, to people, that I fit the bill”: Perspectives on weight and shape control behaviors among low-income, ethnically diverse young transgender women

Abstract: The impact of societal femininity ideals on disordered eating behaviors in non-transgender women has been well described, but scant research has explored these processes among transgender women. The present study explored weight and shape control behaviors among low-income, ethnically diverse young transgender women at high risk for HIV or living with HIV in a Northeastern metropolitan area. Semi-structured in-depth interviews were conducted with 21 participants (ages 18–31 years; mean annual income <$10,000; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 45 publications
(58 reference statements)
0
51
0
Order By: Relevance
“…Qualitative studies have suggested that FTM individuals may use restriction and bulimic behaviors to suppress breasts and hips and that MTF individuals engage in disordered eating to accentuate their femininity and to increase ability to be perceived as cisgender women, thus reducing risk of being targeted for violence and discrimination. 9 , 24–26 Yet, in our sample, FBGNC participants were more likely than MTF participants to report an ED and marginally more likely than FTM participants to report an ED. This may indicate that FBGNC participants are striving to alter gendered features to a greater extent than other transgender groups or that the relationship between body dissatisfaction and EDs is moderated by some factor associated with gender identity in transgender adults.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Qualitative studies have suggested that FTM individuals may use restriction and bulimic behaviors to suppress breasts and hips and that MTF individuals engage in disordered eating to accentuate their femininity and to increase ability to be perceived as cisgender women, thus reducing risk of being targeted for violence and discrimination. 9 , 24–26 Yet, in our sample, FBGNC participants were more likely than MTF participants to report an ED and marginally more likely than FTM participants to report an ED. This may indicate that FBGNC participants are striving to alter gendered features to a greater extent than other transgender groups or that the relationship between body dissatisfaction and EDs is moderated by some factor associated with gender identity in transgender adults.…”
Section: Discussionmentioning
confidence: 49%
“…Using a participatory population perspective to work “with” not “on” transgender communities, the Project VOICE survey instrument and data collection plan were created by a team of community-based advocates, transgender leaders, researchers, and sexual and gender minority policy experts. 9 The survey was designed for a fifth grade reading level. To ensure the integrity and validity of data collected, the survey followed best practices for Internet research with transgender people, including initial usability, pilot testing, and quality management processes to ensure unduplicated responses and valid study respondents.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the study developed by Gordon et al, (2016) investigated the impact of societal femininity ideals on disordered eating behaviours in transgender women. It is worth emphasizing that "transgender women" comprise "those whose gender identitysuch as woman, transwoman, Male to Female (MtF), or genderqueer -differs from their assigned male sex at birth" (Gordon et al, 2016, p. 2).…”
Section: Gender Role Female Sociocultural Standards and Edmentioning
confidence: 99%
“…Diemer, Grant, Munn‐Chernoff, Patterson, and Duncan () concluded that compared to cisgenderstudents, that is, students whose gender identity matches the sex that they were assigned at birth, transgender students are almost five times as likely to report an eating disorder and two times as likely to use unhealthy compensatory methods (e.g., vomiting) for weight control. Gordon, Austin, Krieger, Hughto, and Reisner () found that transgender teenagers are almost three times as likely to restrict their eating, almost nine times as likely to take diet pills, and seven times as likely to take laxatives. This may be due to society's unrealistic standards of the “ideal” body type or to maladaptive coping mechanisms for stress arising from anti‐trans stigma and discrimination.…”
Section: Psychological Well‐being In the Trans Populationmentioning
confidence: 99%